Do Islamic fundamental weighted indices outperform their conventional counterparts? An empirical investigation during the crises in the MENA region - Abadi, Rasha Tawfiq Yousif (2022)
This paper investigates the performance of Islamic fundamental weighted (FW) portfolios compared to that of non-Islamic counterparts, to examine whether Shari'ah-compliant stocks can protect investors during crises in the Middle East and North Africa region. Portfolios' performance is assessed using several risk-adjusted performance measures including more robust measures in the context of recently developed multi-factor models. The study's findings suggest that the performance of Islamic and non-Islamic FW portfolios depends on the performance measures used and on the periods under analysis. Both Islamic and non-Islamic FW portfolios underperform against the cap-weighted benchmark. Furthermore, the Islamic portfolios underperform compared to their non-Islamic counterparts during the period of the global financial crisis, while they perform similarly to their non-Islamic counterparts during the Arab Spring period. Based on these results, we conclude that Islamic FW portfolios do not seem to protect investors from losses during crises.